Pragmatism as Post-Postmodernism Lessons from John Dewey - Hickman, Larry A. (American Philosophy, 2007)
Larry A. Hickman presents John Dewey as very much at home in the busy mix of contemporary philosophy-as a thinker whose work now, more than fifty years after his death, still furnishes fresh insights into cutting-edge philosophical debates. Hickman argues that it is precisely the rich, pluralistic mix of contemporary philosophical discourse, with its competing research programs in French-inspired postmodernism, phenomenology, Critical Theory, Heidegger studies, analytic philosophy, and neopragmatism-all busily engaging, challenging, and informing one another-that invites renewed examination of Dewey's central ideas. Hickman offers a Dewey who both anticipated some of the central insights of French-inspired postmodernism and, if he were alive today, would certainly be one of its most committed critics, a Dewey who foresaw some of the most trenchant problems associated with fostering global citizenship, and a Dewey whose core ideas are often at odds with those of some of his most ardent neopragmatist interpreters. In the trio of essays that launch this book, Dewey is an observer and critic of some of the central features of French-inspired postmodernism and its American cousin, neopragmatism. In the next four, Dewey enters into dialogue with contemporary critics of technology, including Jürgen Habermas, Andrew Feenberg, and Albert Borgmann. The next two essays establish Dewey as an environmental philosopher of the first rank-a worthy conversation partner for Holmes Ralston, III, Baird Callicott, Bryan G. Norton, and Aldo Leopold. The concluding essays provide novel interpretations of Dewey's views of religious belief, the psychology of habit, philosophical anthropology, and what he termed "the epistemology industry."